Corduba, caput provinciae y foco de atracción para las élites locales de la Hispania Ulterior Baetica - Melchor Gil, Enrique (Gerión. Revista de Historia Antigua, 2006)
In this work, we try to demonstrate that Corduba was a centre of attraction for the local elites of different cities of Hispania Ulterior Baetica. A significant number of members of the local oligarchies of the province decided emigrating to the provincial capital in a certain moment of their lives, looking for establishing relations with members of the imperial administration (senatorial and equestrian), promoting themselves to some of higher ordines, or simply culminating their political careers with the prestige provided by holding magistratures in Colonia Patricia.